Should Google offer an online screening test for depression?. (13th September 2017) - Duckworth, Ken; Gilbody, Simon
Abstract : It could raise awareness to improve identification and treatment of depression, says Ken Duckworth, but Simon Gilbody worries that screening for depression is not recommended because it could cause harm